1968
DOI: 10.1677/joe.0.0400337
|View full text |Cite
|
Sign up to set email alerts
|

Repletion of Vasopressin and Oxytocin in the Posterior Lobe of the Pituitary Gland of the Rat

Abstract: Rats deprived of drinking water for 7 days showed a striking depletion of neurohypophysial hormones from the posterior lobe of the pituitary gland. The average daily depletion rate was estimated to be 93 m-u. for vasopressin and 97 m-u. for oxytocin. When rats were allowed free access to water, dehydration was rapidly corrected as shown by normal haematocrit values and plasma osmolarities. Repletion of neurohypophysial hormones, rapid in the first 24 hr., continued gradually thereafter. The mean calculated rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1969
1969
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…Because previous biochemical experiments have suggested that newly formed NSG are likely to be found in the nerve endings and in the hope of reinforcing our biochemical data, we have used morphometry, to analyze the movement Received: March 9, 1984 Accepted after revision: May 11, 1984 of the populations of NSG within the neural lobe during and after increased hormone release. This was produced by water deprivation, a powerful stimulus for the release of both vasopressin and oxytocin [6,10,25,34].The present work shows firstly that, during the first days of dehydration, neurohypophysial hormone release is linked to a loss of NSG from the nerve endings. Those gran ules found in the nerve swellings are only later mobilized for secretion.…”
mentioning
confidence: 51%
“…Because previous biochemical experiments have suggested that newly formed NSG are likely to be found in the nerve endings and in the hope of reinforcing our biochemical data, we have used morphometry, to analyze the movement Received: March 9, 1984 Accepted after revision: May 11, 1984 of the populations of NSG within the neural lobe during and after increased hormone release. This was produced by water deprivation, a powerful stimulus for the release of both vasopressin and oxytocin [6,10,25,34].The present work shows firstly that, during the first days of dehydration, neurohypophysial hormone release is linked to a loss of NSG from the nerve endings. Those gran ules found in the nerve swellings are only later mobilized for secretion.…”
mentioning
confidence: 51%
“…rather than m-u./final body wt. (Simon, 1934;Moses, 1963;Young & van Dyke, 1968) since the animals lose weight during the experiment, partly because of loss of appetite, and fasting alone has been shown not to result in a loss of hormone from the gland (Simon, 1934;Young & van Dyke, 1968 experiments with yet another strain of rats (mean content 405 m-u./100 g) Heller & Lederis (1959) found no significant change after dehydration for 24 hr. In contrast to the effects on vasopressin content, the rate of depletion of pituitary oxytocin caused by 'saline treatment' was significantly different from that caused by water deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Water deprivation has been shown to be a potent stimulus to the hypothalamo-neurohypophysial system, resulting in a depletion of stored hormones from the neural lobe (Ames & van Dyke, 1950;Hild & Zetler, 1953;Gaunt, Lloyd & Chart, 1957;Dicker & Nunn, 1957; Lederis, 1962 ;Young & van Dyke, 1968). However, thistreatmenthasthe disadvantage that experiments must be relatively short term.…”
Section: Introductionmentioning
confidence: 99%
“…The CRF effect of 0.2 equivalents of a neural lobe ex tract from normal rats is 140± 11% (n = 8) of the CRF effect of 150 mlU oxytocin plus 150 mlU vasopressin. These amounts represent 20% (0.2) of the oxytocin and vasopressin content of a neural lobe of normal rats [15]. Thus, extracts of neural lobes have 40-70% more CRF activity than oxytocin and vasopressin contained in the extracts.…”
Section: Crf Extractsmentioning
confidence: 94%